Improving the TNM classification: Findings from a 10‐year continuous literature review. Issue 2 (15th January 2014) - Webber, Colleen; Gospodarowicz, Mary; Sobin, Leslie H.; Wittekind, Christian; Greene, Frederick L.; Mason, Malcolm D.; Compton, Carolyn; Brierley, James; Groome, Patti A
<x xml:space="preserve">Abstract</x> The Union for International Cancer Control's (UICC) TNM classification is a globally accepted system to describe the anatomic extent of malignant tumors. Since its development seventy years ago, the TNM classification has undergone significant revisions to reflect the current understanding of extent of disease and its role in prognosis. To ensure that revisions are evidence‐based, the UICC implemented a process for continuous improvement of the TNM classification that included a formalized system for submitting proposals for revisions directly to the UICC and an annual review of the scientific literature on staging that assessed, criticized or made suggestions for changes. The process involves review of the proposals and literature by a group of international, multidisciplinary Expert Panels. The process has been in place for 10 years and informed the development of the 7th edition of the TNM classification published in 2009. The purpose of this article is to provide a description of the annual literature review process, including the search strategy, article selection process and the roles and requirements of the Expert Panels in the review of the literature. Since 2002, 147 Expert Panel members in 11 cancer sites have reviewed over 770 articles. The results of the annual literature reviews, Expert Panel feedback and documentation and dissemination of results are described.